Impact of Social Media on Political Dissent: A Comparative Analysis of USA and Nigeria - Ogba, Michael Chinonso; Akogwu, Chukwunonso Joseph (Kashere Journal of Politics and International Relations, 2023)
From the purview of most democratic countries and the United Nation’s Charter on Human Rights across the world, citizens have fundamental right of freedom to privately or publicly express their approval, disproval or objection over issues through dissent such as protests, demonstrations revolutions as well as boycotts, amongst others. Such actions have proven to, in most times, inspire positive change, improve accountability and help to define and protect civic space across the globe. Social media networking sites such as Twitter, Facebook, Instagram amongst others have played fundamental role as crucial medium of expression and social change. Thus, through these social media platforms, democratic nations like USA and Nigeria have witnessed an encouraged deployment of engaged and informed citizenry and equally enabled direct participation in public policies. However, for the countries under study: USA and Nigeria, the usage of and control of power and approach to dissent differed considerably The study recommends government sincere approach in creating forum for free speech and critical political discourses for social media users as obtainable in USA. More so, the study recommends the ore-orientation of the people of Nigeria for the proper and impactful use of the social media for social good.